Evolutionary loss of a signalling colour is linked to increased response to conspecific chemicals - Vital Garcia, Cuauhcihuatl (2021)
Behavioural responses to communicative signals combine input from multiple sensory modalities and signal compensation theory predicts that evolutionary shifts in one sensory modality could impact the response to signals in other sensory modalities. Here, we conducted two types of field experiments with 11 species spread across the lizard genus Sceloporus to test the hypothesis that the loss of visual signal elements affects behavioural responses to a chemical signal (conspecific scents) or to a predominantly visual signal (a conspecific lizard), both of which are used in intraspecific communication. We found that three species that have independently lost a visual signal trait, a colourful belly patch, responded to conspecific scents with increased chemosensory behaviour compared to a chemical control, while species with the belly patch did not. However, most species, with and without the belly patch, responded …